Chapter A city of ruins: on photographic documentation of wartime Warsaw - Ferenc, Tomasz (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The destruction of cities in times of war conflicts is usually accompanied by various forms of photographic recording. Such photos are created for various reasons and there is also a range of their subsequent uses. The 20th century is full of the histories of cities destroyed as a result of planned, massive attacks; among them, Warsaw occupies a special position. During the Second World War, its almost complete destruction took place in three stages: the German siege in 1939, the liquidation of the ghetto in 1943, and during the pacification of the Warsaw Uprising in 1944. Each of these tragic events has its photographic representation. The analysis of the three sets of photos is intended to answer several questions: for what purpose they were taken, how their meaning has changed over time, and what is their value as “reference points” and in John Tagg’s depiction of a symbolic “currency”.